Reconciling female agentic advantage and disadvantage with the CADDIS measure of agency. - Ma, Anyi; Rosette, Ashleigh Shelby; Koval, Christy Zhou (Journal of Applied Psychology, 2022)
ndependent agency, and Self-assured agency). We theorized that these agency factors represented distinct agency prescriptions and proscriptions for men and women. In Studies 3-5, we found that this six-factor conceptualization of agency not only reconciles existing tensions within the gender and leadership literature, but also leads to a different understanding of past conclusions-an agentic advantage occurs when women are perceived to possess competent agency, diligent agency, and independent agency, and an agentic disadvantage occurs when women are perceived to possess dominant agency. (PsycInfo Database Record (c) 2022 APA, all rights reserved).